(untitled) (Philological Studies, 2019)
Health care in a country is one of the important elements for preserving and improving people’s health and their living and working environment, and for protection of their living standards and social safety. A great thinker once said: “Society with poor and bad education and bad health system will always be poor”. The history of the health and medical culture in Macedonia including the social health and medical conditions in the 19th century has shown that pioneer steps in this respect were made and in Thessalonica at the time. This mostly applies to the midcentury when the Ottoman authorities started introducing the first laws on organization of health care. That step was only one amongst measures not only intended for protection of the Ottoman armies but the population in the Empire as well. In 19th century epidemic of the plague in the Thessalonica had destructive effect upon of the people in the city. The issue of the taking care ill was part of the positive measures for the prevention of the infectious diseases.